Sistem Peradilan Pidana Pernikahan Dibawah Umur dalam Perspektif HAM - M, Andi Sanjaya; Saimma, Ika Dewi Sartika; Sudarto, Sudarto (LITERATUS, 2025)
This study aims to answer several questions about what causes early marriage and how early marriage affects family life in the concept of human rights. The method used in this study is library research, namely a special search for the purpose of collecting information and logical work that focuses on the object of research and library information, or focuses on solving fundamental problems. The Declaration of Human Rights not only regulates family security, but also states that adult men and women have the right to marry and form a family without restrictions on nationality or religion. Marrying young or marrying at a young age can result in the end of children's education and reduce children's opportunities for physical development, therefore it is considered a violation of human rights. Child Marriage, both male and female, tends to attack women's human rights. The rights of neglected children are also the right to education, the right to growth, development and health. Manipulation of the age of marriage does not actually solve the problem, but creates a new problem, namely that children are not psychologically ready to marry young or underage in the domestic and internal areas.